A Genome-Wide Arrayed cDNA Screen to Identify Functional Modulators of α7 Nicotinic Acetylcholine Receptors. (February 2017) - Rex, Elizabeth B.; Shukla, Nikhil; Gu, Shenyan; Bredt, David; DiSepio, Daniel
Cellular signaling is in part regulated by the composition and subcellular localization of a series of protein interactions that collectively form a signaling complex. Using the α7 nicotinic acetylcholine receptor (α7nAChR) as a proof-of-concept target, we developed a platform to identify functional modulators (or auxiliary proteins) of α7nAChR signaling. The Broad cDNA library was transiently cotransfected with α7nAChR cDNA in HEK293T cells in a high-throughput fashion. Using this approach in combination with a functional assay, we identified positive modulators of α7nAChR activity. We identified known positive modulators/auxiliary proteins present in the cDNA library that regulate α7nAChR signaling, in addition to identifying novel modulators of α7nAChR signaling. These included NACHO, SPDYE11, TCF4, and ZC3H12A, all of which increased PNU-120596-mediated nicotine-dependent calcium flux. Importantly, these auxiliary proteins did not modulate GluR1(o)-mediated Ca flux. To elucidate a possible mechanism of action, we employed an α7nAChR-HA surface staining assay. NACHO enhanced α7nAChR surface expression; however, the mechanism responsible for the SPDYE11-, TCF4-, and ZC3H12A-dependent modulation of α7nAChR has yet to be defined. This report describes the development and validation of a high-throughput, genome-wide cDNA screening platform coupled to FLIPR functional assays in order to identify functional modulators of α7nAChR signaling.